Do English Education Department Students Experience Communication Apprehension? An Investigation of Their Level and Strategies - Nafisah Endahati (Universitas PGRI Yogyakarta, 2023)
In recent decades, investigation on students’ communication apprehension has emerged after being abandoned. It is believed classroom interaction in oral competency consists of students’ activities which mainly facilitate them to develop their communication skill. However, not all students have the same ability in communication. This study aims to investigate the students’ level of communication apprehension and their strategies used to overcome. The Personal Report of Communication Apprehension-24 instrument was used to measure students’ level of communication apprehension, and was analyzed with quantitative descriptive. Interview was conducted to find out their strategies to overcome it. The data collection method was carried out by distributing to 20 respondents, the English education department students of Universitas PGRI Yogyakarta. The obtained data in the form of questionnaire transcription was analyzed as its formula, while interview data was be analyzed through data reduction, data display, and conclusion drawing/verification. The results showed that 5 students were categorized as low level, 3 students were in average level, and 12 students experienced in the high level. Efforts done by students to overcome the communication apprehension are cognitive, affective and social strategies. Based on the findings, it can be declared that majority of students experienced high level of communication apprehension and they preferred affective strategy to reduce communication apprehension. Findings of the research demanded the lecturers conduct meaningful activities such as group discussion to promote autonomous students’ communication practice.